Treatment efficiency of acid mine drainage by the ho-nam coal mine passive treatment system - Ji, S.; Lim, G.; Cheong, Y.; Yoo, Kyoungkeun (Taylor & Francis, 2012)
The Ho-nam coal mine passive treatment system, which consists of an oxidation pond, successive alkalinity producing system (SAPS) and aerobic wetland, was investigated to estimate the treatment efficiency of the entire system and each treatment step. After the acid mine drainage of Ho-nam coal mine moves through the entire system, metal concentration and acidity decreases and alkalinity increases. Acid mine drainage has been treated successfully by the Ho-nam coal mine passive treatment system. However, iron ions were not removed sufficiently in the oxidation pond even though ferrous ions oxidized to ferric ions. Furthermore, in SAPS, Fe concentration decreased rapidly but sulfate reducing bacteria activity was not shown in the system. These results suggest that the objectives of each step were not achieved as designed, although the system was found to be successful.